The Infulence on Hypermobility on Children with Increased Femoral Anteversion: Static and Dynamic Foot Pressure Behavior - Akalan, Ekin; Kurt, Rengin Aslıhan; Sert, Rukiye; Leblebici, Gökçe; Kuchimov, Shavkat Nadir; Bilgili, Fuat; Temelli, Yener; Miller, Freeman; ÖNERGE, KÜBRA; APTİ, ADNAN (My University, 2018)
Increased femoral anteversion (IFA) is the forwardly rotated femoral head relative to transcondilar axis of the knee(1). IFA and hypermobility syndrome are seen together in pediatric clinic(2). For IFA children, effects of hypermobility on plantar pressure behavior during walking are absent in the literature.